Biodiesel production in the presence of sulfonated mesoporous ZnAl2O4 catalyst via esterification of palm fatty acid distillate (PFAD) - Soltani, Soroush; Rashid, Umer; Yunus, Robiah; Yap, Taufiq Yun Hin (Elsevier, 2016)
Methyl ester produced by esterification of palm fatty acid distillate (PFAD) is considered as a non-toxic alternative and biodegradable source of energy. In this work, a polymeric mixed metal oxide with different (Al/(Zn + Al) molar ratio was initially synthesized as a parent mesoporous ZnAl2O4 material. Then, a post-sulfonation treatment was established to prepare a polymeric solid acid SO3HZnAl2O4 catalyst with certain sulfonation degree. The physicochemical, structural, textural, thermal stability characteristics of the synthesized mesoporous catalysts were investigated by X-ray diffraction (XRD), surface area analysis (Brunauer–Emmett–Teller equation), Fourier transform infrared (FT-IR) spectroscopy, temperature programmed desorption (TPD) and thermogravimetric analysis (TGA). The optimized mesoporous SO3HZnAl2O4 catalyst possesses unique properties such as a surface area of 352.39 m2 g−1, the average pore diameter of 3.10 nm, a total pore volume of 0.13 cm3 g−1, and high acid density up to 1.95 mmol g−1, simultaneously. The catalytic activity of the synthesized catalyst was further examined through the esterification of PFAD, containing high free fatty acid (FFA around 90%), resulted in PFAD methyl ester yield of 94.65%. The combination of unique textural properties allows the diffusion of reagents easily into inner acid sites. Moreover, the polymeric mesoporous SO3HZnAl2O4 catalyst was able to be reused for eight consecutive cycles without substantial losses of activity.